Forest road erosion - J. Dobiáš (Journal of Forest Science, 2005)
The forest road network influences surface runoff of uninfiltrated precipitation water on forest lands, mainly in hilly and mountainous areas. This water flows onto the road crown in unpaved forest roads that do not have any ditches. Dragging of extracted logs causes mechanical damage to the crown of unpaved forest road, and tracks after tractor wheels and furrows after dragged logs originate. Flowing water is accumulated in these depressions and the water stream causes erosion. The method for evaluation of conditions for the origination and degree of this erosion damage consists in the calculation of tangential stresses near the bottom at various depths of water and various gradients of road. Limit gradients of road for the origination of greater or smaller damage by erosion for the subsoil grain of various sizes are determined by a comparison of calculated tangential stresses with critical tangential stresses. Rates of discharge were calculated for the particular models of damage.